Surface- and tip-enhanced Raman spectroscopy of DNA. Issue 1 (2010) - Hennemann, L. E.; Meixner, A. J.; Zhang, D.
Abstract : Calf thymus DNA adsorbed on a rough gold substrate or on an atomically smooth gold (111) surface has been investigated by collecting its unique Raman fingerprints using either surface-enhanced Raman scattering (SERS) or tip-enhanced Raman scattering (TERS). A monolayer coverage of DNA strands adsorbed at both the irregular rough edges of evaporated gold grids and at gold nanoparticles is detected by SERS. Highly improved sensitivity down to single DNA strand spectroscopic determination is accomplished by TERS providing an enhancement factor of at least 1400. Based on our experimental results, we propose that TERS is a promising technique to study the DNA–drug molecule interaction on the level of a single DNA strand.